2012
DOI: 10.1111/boc.201100070
|View full text |Cite
|
Sign up to set email alerts
|

TI‐VAMP/VAMP7 is the SNARE of secretory lysosomes contributing to ATP secretion from astrocytes

Abstract: Background information. ATP is the main transmitter stored and released from astrocytes under physiological and pathological conditions. Morphological and functional evidence suggest that besides secretory granules, secretory lysosomes release ATP. However, the molecular mechanisms involved in astrocytic lysosome fusion remain still unknown.Results. In the present study, we identify tetanus neurotoxin-insensitive vesicle-associated membrane protein (TI-VAMP, also called VAMP7) as the vesicular SNARE which medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 46 publications
(86 reference statements)
2
84
0
Order By: Relevance
“…44 The marker protein of secretory lysosomes as the major vesicular compartment for Ca 2C -regulated exocytosis from astrocytes 45 is VAMP7/TI-VAMP (vesicle associated membrane protein 7). 46 Verderio et al (2012) 47 report that VAMP7 is the SNARE of secretory lysosomes contributing to ATP secretion from astrocytes. Considering that ATP is a cytosolic protein, which can be secreted from astrocytes following Ab treatment, 48 and that ATP is known as a protein secreted via an autophagy-based unconventional secretory pathway, 49 VAMP7 might play a role as a regulatory factor for Ab-induced autophagy-based secretion of IDE.…”
Section: Discussionmentioning
confidence: 99%
“…44 The marker protein of secretory lysosomes as the major vesicular compartment for Ca 2C -regulated exocytosis from astrocytes 45 is VAMP7/TI-VAMP (vesicle associated membrane protein 7). 46 Verderio et al (2012) 47 report that VAMP7 is the SNARE of secretory lysosomes contributing to ATP secretion from astrocytes. Considering that ATP is a cytosolic protein, which can be secreted from astrocytes following Ab treatment, 48 and that ATP is known as a protein secreted via an autophagy-based unconventional secretory pathway, 49 VAMP7 might play a role as a regulatory factor for Ab-induced autophagy-based secretion of IDE.…”
Section: Discussionmentioning
confidence: 99%
“…Further data obtained on cultured and freshly isolated astrocytes showed that astrocytes express a variety of SNARE proteins; R-SNARE (vesicular SNARE) proteins synaptobrevin 2/VAMP2, cellubrevin/ VAMP3 [31,32,[70][71][72][73], tetanus neurotoxin-insensitive VAMP (TI-VAMP)/VAMP7 [74], and QSNARE (target membrane SNARE) proteins; synaptosome-associated protein of 23 kDa (SNAP23), SNAP25, and syntaxins (STX) 1, 2, 3 and 4 [30,65,75]. Besides SNARE proteins, cultured astrocytes also express SNARE-associated proteins such as synaptotagmin 4 [76].…”
Section: Proteins Necessary For Snare-dependent Gliosignal Vesicular mentioning
confidence: 99%
“…3 Pioneering work on VAMP7 knock down and over-expression of its regulatory aminoterminal Longin domain have underlined its importance in several cellular processes in different cell types. VAMP7 dependent trafficking was shown to participate in apical polarity, 4 neurite growth, 5 cell adhesion, 6 transport to lysosome from both early endosomes and TGN, [7][8][9] cell migration, exosome and lysosomal secretion, 10,11 and autophagy. 12, 13 We previously showed the involvement of VAMP7 in polarized apical transport 4,14 and its occurrence in detergent resistant membranes.…”
Section: Introductionmentioning
confidence: 99%